2021
DOI: 10.1002/adem.202100548
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Interference Shielding and Electrothermal Performance of MXene‐Coated Cellulose Hybrid Papers and Fabrics Manufactured by a Facile Scalable Dip‐Dry Coating Process

Abstract: Herein, the electromagnetic interference (EMI) shielding and electrothermal properties of MXene‐coated cellulose hybrid papers (MCPs) and fabrics (MCFs) with high flexibility and low density, which are manufactured by a dip‐dry coating approach, are reported. For this purpose, MCPs and MCFs are fabricated by dipping cellulose papers and fabrics repeatedly into an aqueous dispersion of MXene. The electron microscopic and X‐ray diffraction data reveal that MXene sheets are coated uniformly on the surfaces of cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 71 publications
(131 reference statements)
0
16
0
Order By: Relevance
“…(b, c) Current–voltage curves, (d, e) infrared images and time–temperature curves obtained for MCP and MCF. (Panels a–e) Reprinted with permission from ref . Copyright 2021 John Wiley and Sons.…”
Section: Production Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(b, c) Current–voltage curves, (d, e) infrared images and time–temperature curves obtained for MCP and MCF. (Panels a–e) Reprinted with permission from ref . Copyright 2021 John Wiley and Sons.…”
Section: Production Methodsmentioning
confidence: 99%
“…Scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS) showed that the contact of the conductive fillers was limited due to the higher porosity and bulky structure of the cotton fabric. As a result, continuous conductive channels were not formed in sufficient amounts in the cotton fabric . RGO and conductive polymers were synergistically applied by dip-dry coating to enhance the electrothermal properties of the cotton fabrics.…”
Section: Production Methodsmentioning
confidence: 99%
“…Therefore, the addition of a protective layer outside the conductive layer or the insertion of certain adhesives as the middle layer is usually required during the coating. Coating technique mainly include dip coating [75], spraying [76], screen printing [77], vacuum filtration [78] and electroless deposition (ELD) [79].…”
Section: Coatingmentioning
confidence: 99%
“…[43] MXene (Ti 3 C 2 T x ) was manufactured from MAX (Ti 3 AlC 2 ) powder through a layer delamination method. [31,44] For preparing a mild etching solution, 3.2 g of LiF powder was dissolved in 40 mL of 9 m HCl solution. 2 g of MAX powder was then added slowly to the etching solution at 35 °C, which was stirred for 24 h to remove the Al layer from MAX phase.…”
Section: Preparation Of Hybrid Carbon Nanofibersmentioning
confidence: 99%
“…The fabricated MXene sheets were analyzed to have a plane diameter of 20 ± 10 μm and elemental compositions of 35.7 at% Ti, 28.7 at% O, and 20.3 at% F, and 3.48 at% Cl, and 0.78 at% Al, as reported in the previous study. [44] A series of MXene/PEA-derived HCNFs were manufactured through electrospinning, dip-coating, and carbonization, as schematically represented in Figure 1. For electrospinning of the first step, 16 wt% PEA/PVP dope solution was prepared by dissolving PEA and PVP (70/30 by wt%) in DMF solvent and stirring magnetically at 30 °C for 24 h. The uniformly stirred solution was injected into a 20 mL syringe with an inner diameter of 21 G and then spun into nanofibers under the conditions of an applied voltage of 15 kV, a constant distance of 15 cm between the syringe tip and the collector, and a feed rate of 0.5 mL h −1 .…”
Section: Preparation Of Hybrid Carbon Nanofibersmentioning
confidence: 99%